2018
DOI: 10.1177/0361198118758029
|View full text |Cite
|
Sign up to set email alerts
|

Full-Scale Performance Evaluations of Various Wire-Backed Nonwoven Silt Fence Installation Configurations

Abstract: Silt fences have long been a key component for controlling construction stormwater runoff; nonetheless, many silt fence installations fail to perform in the field as intended. Silt fences are temporary sediment control measures used to retain sediment by impounding runoff and allowing for sedimentation on-site, while simultaneously discharging stormwater runoff at a controlled rate. This study evaluated the performance of eight alternative configurations of the Alabama Department of Transportation (ALDOT) stan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
29
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(34 citation statements)
references
References 16 publications
2
29
0
Order By: Relevance
“…This data was used to assess the overall performance of each SB practice to evaluate their structural performance, sediment retention capabilities, and impacts on water quality. Additionally, findings from this study were compared with results reported by Whitman et al (15) for the most effective nonproprietary, wire-backed nonwoven silt fence installation configuration, which will be referred to as the heavy-duty silt fence (HDSF).…”
Section: Resultsmentioning
confidence: 96%
See 3 more Smart Citations
“…This data was used to assess the overall performance of each SB practice to evaluate their structural performance, sediment retention capabilities, and impacts on water quality. Additionally, findings from this study were compared with results reported by Whitman et al (15) for the most effective nonproprietary, wire-backed nonwoven silt fence installation configuration, which will be referred to as the heavy-duty silt fence (HDSF).…”
Section: Resultsmentioning
confidence: 96%
“…(15 cm) downstream of the trench, thus eliminating downstream post voids. This installation method has been proven to be effective means for improving structural stability and minimizing undermining on common silt fence installations ( 15 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Sediment barriers, sediment basins, construction exit pads, surface roughening, temporary mulching, seeding, erosion control blankets, check dams, and inlet protection practices are some examples of common E&SC practices. However, traditional E&SC practices are not sufficient in removing fine-sized particles, which are difficult to remove from suspension and contribute to turbidity plumes (10)(11)(12)(13). Typically, detention-based practices such as sediment basins and traps are used to capture these fine-graded particles.…”
mentioning
confidence: 99%